Economic Determinants and Consequences of Performance Target Difficulty - Kim, Sunyoung; Matějka, Michal; Park, Jongwon (The Accounting Review, 2023)
ABSTRACT Using data on earnings targets in annual bonus plans, we construct and validate an empirical measure of beginning-of-year target difficulty and show that it is negatively associated with market uncertainty, retention concerns, and Chief Executive Officer (CEO) entrenchment. We then present several findings about the effect of target difficulty on performance and CEO compensation. First, greater target difficulty in annual bonus plans is associated with significantly lower CEO cash compensation as well as with decreases in other compensation awards. Second, moderately challenging targets (neither too easy nor too difficult to achieve) are associated with abnormal reversals in fourth-quarter performance, particularly reductions in fourth-quarter performance after abnormally favorable third-quarter performance. Third, greater target difficulty is associated with higher same-year abnormal earnings but at the same time with lower next-year earnings and stock returns. Combined, our findings suggest that target difficulty is an important incentive design choice that affects performance and executive compensation. Data Availability: Data used in this study are publicly available.